African Cities and International Migration Governance: From Glocal Identities to Multilevel Solutions? - Stürner-Siovitz, Janina (Journal of International Affairs, 2022)
At the Africities Summit 2018, African city representatives discussed the role of local authorities in the UN Global Compacts for Migration and Refugees and adopted the Charter of Local and Subnational Governments of Africa on Migration. At first glance, this municipal engagement may seem surprising, given that most African cities lack mandates for action on migration at the local, let alone the international level. However, in practice, a growing number of migrants and refugees are settling in African cities, whose local authorities are therefore confronted with core issues of international migration governance. Lacking adequate funding, resources and national support, some African cities strive to engage in city diplomacy defending their interests and seeking collaboration at higher levels of governance. To better understand and theorize this empirical development, this article asks, how do African cities claim agency and develop action in regional and global migration governance? Contributing to a multidisciplinary dialogue between migration studies, urban studies and international relations literature, the article seeks to expand research on city diplomacy into an under-researched policy field and to overcome a geographic research bias on cities from the Global North. The analytical framework builds on Acuto’s seminal analysis of an international city identity. Combining a qualitative structuring content analysis of official city declarations and statements with an analysis of 25 expert interviews, the article finds that representatives from African cities present cities as actors holding glocal positions, agency, and responsibilities on questions of urban migration. Building on this actor framing, African city representatives argue that municipal cooperation is essential for ensuring that regional and global migration policy-making reflects local realities and is implemented in outcome-oriented and context-specific ways. City representatives draw on this actor framing to move from calls for agency to proactive and predominantly hybrid forms of action—co-shaping narratives on human mobility, setting transnational municipal standards, and demanding a voice in intergovernmental deliberations.
Keywords: Africa; cities; migration; city diplomacy